2011
DOI: 10.1007/s00044-011-9861-4
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of 3′-indolyl substituted 4H-chromenes catalyzed by DMAP and their antimicrobial activity

Abstract: A new series of indole-based chromene derivatives 4a-4p has been synthesized by one pot cyclocondensation reaction of 2-phenyl-1H-indole-3-carbaldehyde 1a-1h; malononitrile 2; and 1,3-cyclohexanedione/dimedone 3a/b under microwave irradiation catalyzed by an organocatalyst 4-(N,N-dimethylamino) pyridine. Easy experimental procedure, high yield, selectivity, and shorter reaction time are the imperative features of this method. All the compounds were screened against a representative panel of bacteria and fungi.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 56 publications
0
20
0
1
Order By: Relevance
“…It was found that the rate of reaction of ethyl cyanoacetate (3b) with cyclic 1,3-dicarbonyl compounds (10 and 11) was slower than that of malononitrile (3a), possibly because of the lower reactivity of the cyanoacetates. When ethyl acetoacetate (14) was used as enolizable substrate, the reaction proceeded efficiently, and ethyl 6-amino-5-cyano-2-methyl-4-aryl-4H-pyran-3-carboxylate derivatives (15a-g) were formed in high yields (Table 5, entries 24-30).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It was found that the rate of reaction of ethyl cyanoacetate (3b) with cyclic 1,3-dicarbonyl compounds (10 and 11) was slower than that of malononitrile (3a), possibly because of the lower reactivity of the cyanoacetates. When ethyl acetoacetate (14) was used as enolizable substrate, the reaction proceeded efficiently, and ethyl 6-amino-5-cyano-2-methyl-4-aryl-4H-pyran-3-carboxylate derivatives (15a-g) were formed in high yields (Table 5, entries 24-30).…”
Section: Resultsmentioning
confidence: 98%
“…Over the past few years, both these six-membered oxygen-containing heterocycles and their derivatives have attracted much attention, owing to their wide range of biological activity, for example spasmolytic, diuretic, anticoagulant, antianaphylactic [13], antimicrobial [14], antifungal [15], antibacterial [16], antioxidant [17], antileishmanial [18], antitumor [19], local anesthetic [20], antihistaminic [21], and antiallergenic [22] activity and because of their use for treatment of Alzheimer's disease [23] and schizophrenia [24]. Moreover, several chromenes are widely used as pigments [25], cosmetics [26], and laser dyes [27].…”
Section: Introductionmentioning
confidence: 99%
“…The substructure of indole is a key structural motif in a variety of bioactive compounds [8,9]. Therefore, indoyl 4H-chromene has the combined properties of both indole and chromene moieties that provide new promising biological activities [10,11]. Many methods have been presented for the synthesis of these derivatives and various catalysts have been used, such as ZnO nanoparticle, polystyrene-supported p-toluenesulfonic acid, 4-dimethylaminopyridine (DMAP), β-cyclodextrin, oleic acid, 1,4-diazabicyclo[2.2.2]octane (DABCO), microbial cyclosophoraose, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Muitos estudos na literatura empregaram a radiação micro-ondas em diferentes metodologias e estratégias sintéticas e comprovaram a eficiência que apresenta em comparação com os métodos convencionais [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Aplicação Da Radiação Micro-ondas Na Condensação De Knoevenagelunclassified
“…Guillot et al [35] Kwon et al [36] Bourahla et al [37] Lingham et al [38] Trilleras et al [39] Kumar et al [40] Fozooni et al [41] _____________________________________________________________________________ …”
Section: Reação Referênciamentioning
confidence: 99%